Identifying the location of a concealed object through unintentional eye movements - Neuman, Yair; Assaf, Dan; Israeli, Navot (Frontiers in Psychology, 2015)
In some investigative and interrogative contexts, the investigator is seeking to identify the location of an object (e.g. implanted bomb) which is known to a given subject (e.g. a terrorist). In this paper, we present a non-intrusive methodology for uncovering the loci of a concealed object by analyzing the subject's eye movements. Using a combination of eye tracking, psychological manipulation and a search algorithm, we have performed two experiments. In the first experiment, we have gained 58% hit rate in identifying the location of the concealed object and in the second experiment 56% hit rate. The pros and cons of the methodology for forensic investigation are discussed.